2017
DOI: 10.1111/cid.12517
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year clinical prospective follow‐up of extrasinus zygomatic implants for the rehabilitation of the atrophic maxilla

Abstract: This 3-year clinical follow-up study indicates that extrasinus zygomatic implants represent predictable treatment option atrophic maxillae. Further longitudinal prospective clinical studies are necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 13 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…Their potential safety and effectiveness make them a very interesting subject for future trials, as found by observational studies. 10,44,45 32 The inclusion of preference trials may mitigate such issues, by rendering study participants closer to real patients, with freedom to deliberate on which treatment they will receive. 46,47 The paucity of studies makes any assumption This systematic review innovates by its patientcentered focus, which is uncommon in other reviews.…”
Section: Results Show No Evident Difference Regarding Peri-mentioning
confidence: 99%
See 2 more Smart Citations
“…Their potential safety and effectiveness make them a very interesting subject for future trials, as found by observational studies. 10,44,45 32 The inclusion of preference trials may mitigate such issues, by rendering study participants closer to real patients, with freedom to deliberate on which treatment they will receive. 46,47 The paucity of studies makes any assumption This systematic review innovates by its patientcentered focus, which is uncommon in other reviews.…”
Section: Results Show No Evident Difference Regarding Peri-mentioning
confidence: 99%
“…The maxillary arch poses specific challenges, including low-density bone 9 and limiting sinus anatomy. 10 Furthermore, fixed prostheses are a more intuitive choice for edentulous maxillae, given that patient satisfaction does not seem to improve much with maxillary overdentures. 11 The possibility of immediate load after implant insertion can expedite an otherwise time-consuming treatment, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the results of our study indicate efficacy of immediate loading of extra‐sinus zygomatic implants which is the major benefit for the patient and treating team . Prosthetic loading 3‐6 months after surgery is also very popular among authors doing similar research.…”
Section: Discussionmentioning
confidence: 54%
“…This technique uses a lateral slot outside the wall of the maxillary sinus, avoiding or minimizing the contact of the implant with the sinus membrane. This technique reduced considerably the surgical time and improved the emergence prosthetic profile, due to moving the implant platform nearer to the bone crest, in an optimal 3dimensional position for the implant-supported restoration [25]. This procedure, called "Sinus Slot Technique" places the zygoma platform directly over the alveolar ridge, very similar to standard dental implants [51].…”
Section: Discussionmentioning
confidence: 99%